2023
DOI: 10.3390/su152416708
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Mechanisms by Which Digital Platforms Influence Family-School Partnerships among Parents of Young Children

Pi-Chun Hsu,
Ru-Si Chen

Abstract: This research delved into the correlation between digital platforms and the dynamics of family-school collaboration within the context of parents with young children in Taiwan. It also examined the roles of parental involvement, teacher-child interactions, and online communication in this model. In the context of Taiwan, a research endeavor was undertaken to elucidate the viewpoints of parents with preschool-age children concerning digital platforms and their associated determinants. A Chinese-translated quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(79 reference statements)
0
0
0
Order By: Relevance
“…These results suggest that the implementation of a communication application may have contributed to positive changes in parent-child relationships, with parents feeling more connected to their children throughout the day and using the information shared to strengthen parent-child communication practices. This finding is consistent with previous research that has found that parent-educator digital communication can support observant intimacy within parent-child relationships through enhanced understanding of a child's day [11,51]. Perhaps CMC can influence the development of a particular relationship that is the focus of the communication.…”
Section: Discussionsupporting
confidence: 91%
“…These results suggest that the implementation of a communication application may have contributed to positive changes in parent-child relationships, with parents feeling more connected to their children throughout the day and using the information shared to strengthen parent-child communication practices. This finding is consistent with previous research that has found that parent-educator digital communication can support observant intimacy within parent-child relationships through enhanced understanding of a child's day [11,51]. Perhaps CMC can influence the development of a particular relationship that is the focus of the communication.…”
Section: Discussionsupporting
confidence: 91%
“…Technology serves as a catalyst for enhancing parental involvement in the education of their children, fostering a robust partnership between home and school (Hsu & Chen, 2023). With the advent of specialized applications or portals, parents now have the capability to closely monitor the academic progress of their children, engage in seamless communication with teachers, and actively participate in various school-related activities.…”
Section: Finding and Discussionmentioning
confidence: 99%